2021
DOI: 10.3390/jcm10163716
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of EUS-Guided Fine-Needle Aspiration Biopsy for Gastric Linitis Plastica with Negative Endoscopic Biopsy

Abstract: Due to the tendency of gastric linitis plastica (GLP) to cause extensive submucosal infiltration, a superficial endoscopic biopsy sometimes yields no evidence of malignancy, hindering definite diagnosis. The present study was a single-center retrospective analysis of 54 consecutive patients diagnosed with GLP between 2016 and 2020 to evaluate EUS-guided fine-needle aspiration (EUS-FNA) biopsy outcomes in patients with negative endoscopic biopsy findings. A pathological GLP diagnosis was achieved by endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Furthermore, the mean duration of these studies was 64 months (standard deviation [SD], 16 months). These four studies were single‐center, retrospective studies and consisted of patients with suspected SGC 8,9,13,14 . The mean overall quality by NOS for the four included studies was 5.5 (SD = 0.58; Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the mean duration of these studies was 64 months (standard deviation [SD], 16 months). These four studies were single‐center, retrospective studies and consisted of patients with suspected SGC 8,9,13,14 . The mean overall quality by NOS for the four included studies was 5.5 (SD = 0.58; Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…4). 13 13 (100) 10 (76.9) N/A ‡ N/A ‡ 0 (0) Assaf A et al 14 10 (100) 9 (90) 3 3 (100) 0 (0) † EUS-FNA diagnostic proportion for scirrhous gastric cancer (definitive diagnosis by EUS-FNA/ patients with SGC). ‡ Details regarding lymph node metastasis were not specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the European Society of Gastrointestinal Endoscopy recommends a MIAB or EUS-FNB for the tissue diagnosis of subepithelial lesions, including gastrointestinal stromal tumor (GIST)[ 14 ], there is no standard method for making a tissue diagnosis of GLP. In the previous articles, an EUS-FNB for GLP cases with a negative endoscopic biopsy was reported to be useful in that EUS could directly visualize whether or not the target had been punctured properly, and the positive rates were high with few adverse events (Table 2 )[ 13 , 15 - 17 ]. However, Zhou et al [ 18 ] conversely reported that the diagnostic yield of EMR with the bite-on-bite technique for gastric-infiltrating tumors, including GLP, was 82.2% (23/28).…”
Section: Discussionmentioning
confidence: 99%